RELATIONSHIP BETWEEN TUBERCULOSIS AND STUNTING IN TODDLERS AT THE PEDIATRIC CLINIC OF DUSTIRA HOSPITAL - Jasmine Shafa Dzakira; Yoke Ayukarningsih; Siska Telly Pratiwi (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2026)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. TB is one of the chronic infections that can affect the nutritional status of toddlers. Children suffering from TB are at risk of experiencing stunting. This study aimed to determine the relationship between tuberculosis and stunting among toddlers attending the Pediatric Clinic of Dustira Hospital. This research employed an analytical method with a cross-sectional design involving 90 toddlers aged 24–59 months at the Pediatric Clinic of Dustira Hospital. The study utilized secondary data obtained from the medical records of patients from the Pediatric Clinic of Dustira Hospital during the 2021–2022 period. Data were analysed using univariate and bivariate analyses with the chi-square test. The results showed that 17.7% of toddlers with TB experienced stunting. Statistical analysis indicated a significant relationship between TB and the incidence of stunting among toddlers (p-value = 0.044). Toddlers with TB were found to be 4.65 times more likely to experience stunting. TB, as a chronic disease, is associated with malnutrition in toddlers. Chronic malnutrition leads to a decrease in the linear growth rate as the body attempts to compensate in order to maintain its nutritional status. This linear growth retardation can progress into stunting or even severe stunting. Keywords: stunting, toddlers, tuberculosis DOI : 10.35990/mk.v9n1.p35-44